The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.3346/jkms.2005.20.3.489
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of Ki-67 Labeling Index in Pituitary Macroadenoma

Abstract: The aim of our study was to investigate the correlation of the proliferative activity of pituitary neoplasms with clinical characteristics and recurrences. Tumor specimens were obtained from 44 consecutive patients with pituitary macroadenomas who underwent surgery between July 1998 and August 2003. Specimens were immediately fixed in 10% buffered formalin and then embedded in paraffin. The Ki-67 antigen was assessed by immumohistochemical analysis using the monoclonal antibody. We investigated the correlation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
5
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 29 publications
(51 reference statements)
1
46
5
1
Order By: Relevance
“…Invasive pituitary adenomas that exhibit relatively higher mitotic activity, MIB-1 labeling index of [ 3 %, and excessive p53 immuno-reactivity are classified as atypical adenomas by the World Health Organization [6,9]. Furthermore, these atypical adenomas have been associated with higher risk of recurrence or lack of therapeutic response [9,10,13]. Our study found a statistically significant difference in the proliferation marker MIB-1 as well as the ADC values in invasive pituitary adenomas as compared to noninvasive pituitary adenomas.…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations
“…Invasive pituitary adenomas that exhibit relatively higher mitotic activity, MIB-1 labeling index of [ 3 %, and excessive p53 immuno-reactivity are classified as atypical adenomas by the World Health Organization [6,9]. Furthermore, these atypical adenomas have been associated with higher risk of recurrence or lack of therapeutic response [9,10,13]. Our study found a statistically significant difference in the proliferation marker MIB-1 as well as the ADC values in invasive pituitary adenomas as compared to noninvasive pituitary adenomas.…”
Section: Discussionmentioning
confidence: 57%
“…Markers of cell proliferation, such as the immunohistochemical detection of Ki-67 antigen have been suggested as biomarkers for aggressive behavior in atypical pituitary adenomas [3,9,10]. Ki-67 is a nuclear antigen expressed in proliferating cells identified by monoclonal antibody MIB-1 [10].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The MKI67 expression is correlated with neoplasm recurrence and visual field defect (Paek et al, 2005). Additionally, it is believed to be an independent predictor of pituitary adenomas' progression after surgery (Gejman et al, 2008).…”
Section: Notementioning
confidence: 99%